AB0102 Antiphospholipid syndrome (aps) in children. (1st June 2001) - Pombo, ME; Merino, R; Pascual, D; Cuesta, MV; Aguado, A; García-Consuegra, J
Abstract : Background: Objectives: To evaluate clinical features and management options of persistent antiphospholipid antibodies (aPL) in children. Methods: Retrospective chart review of patients, seen between 1987 and 2000. Results: Six patients with ages at diagnosis ranging from 9 to 13 years are presented. One of them with primary APS and 3 with SLE and asymptomatic aPL. The clinical manifestations are shown in the Table 1 . All of the patients included were positive for lupus anticoagulant and all of them except the case 4 had positive tests for aCL and Aβ2GPI . Conclusion: In paediatric patients with aPL, the risk of thrombosis, their recurrences and the management of oral anticoagulation may be different from adults.